ANALYSIS OF VOLTAGE DROP USING CAPACITOR COMPENSATION IN THE 150 KV SYSTEM AT THE DUMAI INDUSTRIAL AREA SUBSTATION - Saputra, Aidil; Erhaneli, Erhaneli; Warmi, Yusreni; Dewi, Arfita Yuana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
The 150 kV substation at PT. PLN (Persero) Central Sumatra Load Control Unit (UP2B SUMBAGTENG), particularly the Dumai Industrial Area (KID) substation, often experiences significant voltage drops, especially during peak load times.. Voltage drops occur due to high consumer loads and network length with an average of 139 kV during WBP at the end of the GI. The voltage recorded at GI KID averages 139 kV during WBP and can drop to 130 kV (-13.3% of its nominal 150 kV voltage), while on holidays or outside WBP the average voltage increases to 148 kV, approaching the nominal 150 kV. This condition has an impact on the quality of electric power and consumer satisfaction, especially for industrial customers and business centers with high power needs. This study aims to analyze the causes of voltage drops and provide solutions to keep the system voltage stable according to SPLN No. 1:1995 (-10% to +5%). The proposed solution is the installation of capacitor banks in parallel on the 150 kV BUSBAR GI KID. The simulation results show that the installation of a 1×25 MVAr capacitor increases the voltage at 10:00 from 143 kV to 151.4 kV (+5.9%), at 16:00 from 140 kV to 148.6 kV (+6.1%), and at 19:00 from 130 kV to 139.3 kV (+7.1%). The installation of a 2×25 MVAr double capacitor increases the voltage even higher: at 10:00 to 160.5 kV (+12.2%), at 16:00 157.8 kV (+12.7%), and at 19:00 to 148.8 kV (+14.5%), demonstrating the effectiveness of reactive power compensation to overcome voltage drops. By implementing a capacitor bank, the voltage can be controlled so that PT. PLN (Persero)'s electrical equipment and consumer equipment remain safe, equipment disruptions can be minimized, and lighting is not dim. This solution is more appropriate for customers with large loads, such as industrial and business centers, because their reactive power requirements are significant, while household customers are generally regulated through distribution networks and distribution transformers. This study proves that the use of capacitor banks is effective in improving voltage quality, preventing undervoltage, and maintaining voltage stability on the 150 kV radial network, especially in the KID Substation.Keywords: voltage drop, capacitor bank, 150 kV GI, SPLN, reactive power compensation